Kõlbelistest ja usulistest otsingutest postmoderniseeruvas Eestis - Remmel, Meego (Usuteaduslik Ajakiri, 2002)
Meego Remmel, Ethical and religious search in postmodernist Estonia. Estonia as a historical factor of innovation and complete change of the Soviet Marxist-Leninist empire up to the collapse of the Union itself is providing an interesting and a descriptive pattern also in a new, Postmarxist and Postmodern era. Estonia is small enough and its historical development is relatively clear in order to see it as a model society of cultures under Postmarxist and Postmodernist impacts. Throughout the permanent process of change in Estonia the Christian community has learned how to build upon and stand for their own Christian tradition, narratives, practices, virtues. Living through the Postmarxist philosophical, religious and ethical vacuum, opening to the wider world of pluralism, facing the growth of individualism and Postmodern impacts - all that has taught a lesson to the Estonian Christians. The article, in fact, to be continued in the next issue, presents some sociological insights to the processes of postmodemisation of Estonia. The author is showing how the people in Estonia are facing the challenges of re-evaluation of the society, at the same time indicating how the Estonian Christian community has developed a solid tradition of faith and ethics within the Estonian tradition in itself.